Eating Habit as Lifestyle Predictors of Metabolic Syndrome in Coal Mining Workers - Mufatihatul Aziza Nisa; Ratna Setyaningrum; Fitria Fitria (The Indonesian Journal of Occupational Safety and Health, 2023)
Introduction: Previous study was carried out in a company, obtaining the prevalence of metabolic syndrome cases by 21.58% with non-communicable diseases as the indicator. The cause of the metabolic syndrome is critical to understand in order to reduce the impact of acute non-communicable diseases. Excessive food consumption and low physical activity in office workers and coal mining workers are two risk factors that contribute to the development of metabolic syndrome. Therefore, current research was conducted aiming to identify the lifestyle aspects related to metabolic syndrome in coal mining companies in South Kalimantan. Methods: This study was carried out through analytical observational cross-sectional research. In this case, the data were collected using questionnaires. Exercise routines, cigarette smoking, and meal frequency were the research factors. In South Kalimantan, there are up to 70 employees of mining company, and 22 people of them were selected as the research subjects through purposive random sampling and inclusion criteria. Results: The indicators of metabolic syndrome in most of the respondents showed normal state. However, a small number of respondents were at risk of having the indicators of metabolic syndrome. Meanwhile, based on the statistical analysis, there is a lifestyle factor that correlates with the frequency of eating coconut milk-based chicken curry (1-2 times/week) with metabolic syndrome (p=0.045). Conclusion: Types of food cooked using coconut milk can trigger a person to have a risk of experiencing one or several of the metabolic syndrome indicators. Things that can be done to reduce the risk of metabolic syndrome associated with the frequency of habit of eating high-fat animal side dishes, including reducing the frequency of such food at night.